The Status of Iodine Deficiency in Mehrauli area of South Delhi - Dua, B; Ray, Tapas Kumar; Dhiman, B (Indian Journal of Community Health, 2015)
Background: Iodine deficiency disorders (IDDs) are important public health problem affecting almost the entire country. It means not only goiter but all related disorders of physical growth and brain development. The literature on the magnitude of Iodine deficiency among children in Delhi is limited. Present community based study was conducted to obtain better knowledge on Iodine deficiency in Delhi. Objective: To find out the prevalence of goiter and iodine level in urine and household salt among children of 6-12 years in Mehrauli area of Delhi. Methodology: Both boys and girls of age 6-12 years were selected from all the eight existing wards of Mehrauli, Delhi. A total of 1456 children were examined for goiter .Urine samples for estimating iodine excretion level were collected from 146 children and 292 household salt samples were collected for estimating iodine level in salt. The study subjects were spread over 1016 households. Results: In the study, total goiter rate (TGR) was found to be 1.7% (n=25) which is below the level of WHO defined public health problem. Median urinary iodine excretion level was found to be 248.5µg/l in overall 146 urinary samples ruling out iodine deficiency in the area. Excess iodine (above acceptable levels i.e. >200µg/l) was found to be present in 91 samples (62.3%). However iodine content was found to be adequate in 271 (93%) salt samples. Mean iodine content in salt was found to be 35.7±11.1 ppm. Discussion and conclusion: The urinary and salt iodine content in the study area are above the recommended cut off suggested by WHO/ICCIDD/UNICEF for defining of iodine deficiency disorders. Thus iodine deficiency is no longer a public health problem in the study area. However there is a need for periodic monitoring of salt samples as about 7% of households still consumed salt of below 15 ppm of iodine. Community based awareness campaign may be an effective strategy to motivate more people for consuming iodised salt and knowing about the dangers of iodine deficiency .